Changes of endothelial function and intracardiac hemodynamics during implantation of different types of pacemakers - V. A. Sanakoeva; R. Z. Pashaev; A. A. Pukhaeva; A. G. Avtandilov (Российский кардиологический журнал)
Aim. To determine the dynamics of endothelial function and intracardiac hemodynamics during implantation of different types of pacemakers.Material and methods. The study involved 61 patients, 29 of them were implanted with single-chamber pacemaker (the first group), 32  — two-chamber pacemaker (second group) with sick sinus syndrome (SSS), as well as patients with 2-3 degrees AV conduction disorder. Test with endothelium-dependent vasodilation of the brachial artery was performed using the standard technique and the velocity parameters of blood flow were determined. Parameters of intracardiac hemodynamics and left atrial (LA) function were determined. These studies were conducted in patients initially upon admission to the hospital and 2 months later implantation of pacemaker.Results. Endothelium-dependent vasodilation significantly deteriorated in patients with single-chamber pacemaker which initially was 6,1 [2,74;9,815]% and in 2 months decreased to 5,4 [2,37;7,55]% (p=0,05). There was a tendency to deterioration of left ventricular (LV) contractile function accompanied by a decrease in ejection fraction (EF) to 55,04 [49,04;68,72]%, and decrease emptying fraction of LA to 37,36 [31,67;52,85]%. There was a tendency to increase the volume index of LA which indicates an increasing overload of the volume and pressure of LA. There was a significant increase in the degree of endothelium-dependent vasodilation in patients of the second group initially compiling a 3,25 [2,15;6,61]% and then reaches 6,15 [2,75;8,97]% 2 months after surgery (p<0,04). There was no overload in the volume and pressure of LA and improved indirect signs of LV compliance parameters (growth of end-systolic dimension and volume) and decreased LV EF to 53,23 [44,1;69,95]%. In patients in the first group there was a tendency to increase peripheral resistance to 1227 [1065;1318] dyne x cm-5 x sec, accompanied by a significant decrease in blood flow rate. In the second group there was a tendency to reduce peripheral resistance to 1215 [1136;1391] dyne x cm-5 x sec and a significant increase in blood flow rate. There was a significant correlation between the systole LA dimension and total peripheral resistance in patients with VVI stimulation (r=0,78, p=0,0022), which indicates an increase in total peripheral resistance with a change in blood flow from LA to LV and a decrease in cardiac output.><0,04). There was no overload in the volume and pressure of LA and improved indirect signs of LV compliance parameters (growth of end-systolic dimension and volume) and decreased LV EF to 53,23 [44,1;69,95]%. In patients in the first group there was a tendency to increase peripheral resistance to 1227 [1065;1318] dyne x cm-5 x sec, accompanied by a significant decrease in blood flow rate. In the second group there was a tendency to reduce peripheral resistance to 1215 [1136;1391] dyne x cm-5 x sec and a significant increase in blood flow rate. There was a significant correlation between the systole LA dimension and total peripheral resistance in patients with VVI stimulation (r=0,78, p=0,0022), which indicates an increase in total peripheral resistance with a change in blood flow from LA to LV and a decrease in cardiac output.Conclusion. Endothelial function deteriorates with single-chamber stimulation and improves with two-chamber stimulation. These changes are based on shear stress and nitric oxide endothelium secretion the changes of which depend on the characteristics of central and peripheral hemodynamics.